IRON FORTIFIED PASTEURIZED MILK: PHYSICO-CHEMICAL ATTRIBUTES AND EFFICACY AGAINST IRON DEFICIENCY ANAEMIA IN SPRAGUE DAWLEY RATS - N. Akhter; S. Iqbal; M. Nasir; A. Ashraf; U. Bacha; M. A. Khan (Journal of Animal and Plant Sciences, 2014)
Iron Deficiency Anaemia (IDA) is a serious public health issue involving large number of population around the globe especially from the developing countries. In Pakistan, the iron deficiency is a crucial nutritional problem and almost one fifth of country’s women are suffering. For community based management of IDA, iron fortification in various food commodities is considered to be the best approach. Keeping in mind the importance of this issue, iron fortified pasteurized milk (IFPM) was prepared and its ability to reduce the IDA in Sprague Dawley rats was evaluated. Raw buffalo milk was fortified with FeSO4 at a concentration of 0.0%, 0.04%, 0.06% and 0.08% of milk solids and vitamin C (30mg/100g of milk) followed by pasteurization at 75°C for 16sec. Physico-chemical and sensory attributes of all treatments were not significantly different from control with the exception of vitamin C and iron contents. The improvement of haemoglobin concentration in rats after consumption of fortified milk was found to be statistically significant as compared to control (P≤0.05) and IFPM has increased the haemoglobin level from 9.84 ±0.287 to 14.37±0.325 g/dL in 56 days. It can be concluded from this study that the iron fortification in pasteurized milk does not affect its sensory and physical characteristics and can be helpful to improve IDA.
Keywords: `Pasteurized Milk; Iron Fortification; Iron Deficiency Anaemia